Whey Protein Lipid Concentrate High in Milk Fat Globule Membrane Components Inhibit Porcine and Human Rotavirus in vitro - Monaco, Marcia H.; Gross, Gabriele; Donovan, Sharon M. (Frontiers in Pediatrics, 2021)
Background: The milk fat globule membrane (MFMG) is a complex milk component that has been shown to inhibit rotavirus (RV) binding to cell membranes in vitro. Herein, a whey protein lipid concentrate high in MFGM components (WPLC) and whey protein concentrate (WPC; control) were screened for anti-infective activity against porcine OSU and human Wa strains of RV in both the African Green Monkey kidney (MA104) and the human colorectal adenocarcinoma (Caco-2) cell lines. Materials and Methods: Confluent cells were exposed to OSU or Wa RV in the presence of WPLC or WPC (control) at 0, 0.1, 0.5, 1.0, 2.5 or 5 mg/ml. Infectivity was detected by immunohistochemistry and expressed as % inhibition relative to 0 mg/ml. WPLC efficacy over WPC was expressed as fold-change. One-way ANOVA analyzed data for the independent and interactive effects of concentration, test material, and RV strain. Results: Both WPLC and WPC exhibited concentration-dependent inhibition of human Wa and porcine OSU RV infectivity in MA104 and Caco-2 cells. WPLC was 1.5- to 4.8-fold more effective in reducing infectivity than WPC. WPLC efficacy was independent of RV strains, but varied between cell lines. WPLC and WPC at concentrations ≥ 0.5 mg/mL were most effective in reducing human Wa RV infectivity in MA104 cells. Conclusions: WPLC decreased infectivity of two strains for RV which differ in their dependency on sialic acid for binding to cells. Inhibition was observed in the most commonly used cell type for RV infectivity assays (MA104) and an intestinal cell line (Caco-2). An effect on virus infectivity might be a potential mechanisms of action contributing to beneficial effects of supplementation of infant formula with MGFM reducing the risk of infections and consequently diarrhea incidence in infants.